MEDICINAL PROPERTIES OF SOME PLANTS OF THE POACEAE FAMILY - Abdimuminova Maftuna (Journals Park Publishing, 2022)
This article provides information on the medicinal properties of some plants belonging to the family poaceae.
Keywords: poaceae; fruit; medicine